Fabrication of Carbon Nanotube Reinforced Al2O3/Cr2O3 Nanocomposites by Coprecipitation Process - Jaber, Hussein Alaa (Al-Khwarizmi Engineering Journal, 2017)
In this research, the effect of multi-walled carbon nanotubes (MWCNTs) on the alumina/chromia (Al2O3/Cr2O3) nanocomposites has been investigated. Al2O3/Cr2O3-MWCNTs nanocomposites with variable contents of Cr2O3 and MWCNTs were fabricated using coprecipitation process and followed by spark plasma sintering. XRD analysis revealed a good crystallinity of sintered nanocomposites samples and there was only one phase presence of Al2O3-Cr2O3 solid solution. Density, Vickers microhardness, fracture toughness and fracture strength have been measured in the sintered samples. The results show that the relative density, microhardness and fracture strength of nanocomposites are significantly improved at low contents of Cr2O3 and MWCNTs. The increase of MWCNT’s content in the nanocomposites has adversely affected due to increasing the tangle and interaction of MWCNTs with each other, which leads to agglomeration in the nanocomposites. Increasing of Cr2O3 content in nanocomposites increases formation of Al2O3-Cr2O3 solid solution that actually requires the high sintering temperature to achieve good densification. The fracture toughness of Al2O3/Cr2O3-MWCNTs nanocomposites was enhanced by increasing the carbon nanotube content.